Gambaran Perilaku Caring Perawat Berdasarkan Persepsi Pasien pada Masa Pandemi Covid19 di RSU Kota Pekalongan - Mutiara, Yuni; Priyoggo, Nur Izzah (Prosiding University Research Colloquium, 2022)
Background: Nurses as the frontline who provide health services have an important role, one of the important roles of nurses during a pandemic is to continue to provide active nursing care to patients by providing good caring to patients. Objective: This study aims to determine the description of the caring behavior of nurses based on pa-tient perceptions during the pandemic at the Pekalongan City General Hospital. Sample: The sampling technique used the Accidental Sampling technique which was carried out for 1 month with a total sample of 215 respondents in inpatients at the Pekalongan City General Hospital. Methods: This research method uses a Caring Assessment Tools questionnaire consisting of 20 state-ments, from 20 questionnaires there are 6 negative statements and 14 positive statements. Results: The results showed that more than half, or as many as 148 respondents (58.8%) stated that nurse caring for inpatients was good and 67 respondents (31.2%) indicated that nurse caring for inpa-tients was not good. value 0.000 <0.05 so that the conclusion is that the data is not normal. Conclusion: In this study, it was concluded that the caring behavior of nurses based on the patient’s perception during the pandemic was good Suggestion: For hospitals, it is hoped that the results of this study can be used as a basis for input to hospital management in making nursing service policies to improve quality nursing services.